Evaluation of ascorbic acid levels and other biochemical parameters levels in Local and Imported Lemon Juices. - jwan abdullmuhsin (Al-Qadisiyah Journal of Pure Science, 2020)
Lemon fruit is an important type of Rutaceae family, it has many health benefits due to its important contents. Ascorbic acid (Vitamin C) is a water-soluble vitamin which has reductive properties, so it is used on a large scale as antioxidant in food and drinks. The goal of this search is to determine the concentrations of vitamin C and protein  and minerals (Iron, Magnesium, Potassium , and Calcium) in local and imported lemon juices.Local and imported (from Turkey) lemon were chosen in this study, Ascorbic acid concentration was measured via redox titration method; involve titration with an oxidant solution: dichlorophenol indophenol. Furthermore protein concentration was measured spectrophotometry depending on Biuret method and the minerals by Atomic Absorption Spectrophotometer.The results indicated that local lemon juice is a rich source of vitamin C (24.02±1.07mg/100ml juice) in comparison to the imported lemon. However  the local lemon juice gave a lowest concentration of protein (0.37± 0.21mg/100ml juice). Minerals concentrations were somewhat close when compared between the three studied groups while the pH value was slightly higher in local lemon . Our results indicates that local lemon juice is a highest source of the important antioxidant vitamin (vitamin C) with acceptable acidity .